Advanced Research in Shipping Informatics and Communications - Nikitas Nikitakos; Iosif Progoulakis (Journal of Marine Science and Engineering)
The shipping industry, a vital part of global trade and the maritime transport system (MTS) and a critical infrastructure for all nations, is undergoing a technological evolution through the integration of advanced information and communication technologies [...]